Effects of photobiomodulation on wound contraction in rats undergoing doxorubicin extravasation: a histomorphometric analysis - Freitas, Karina Alexandra Batista Da Silva [UNESP]; Rocha, Noeme Sousa [UNESP]; Minicucci, Eliana Maria [UNESP]; da Silva, Valéria Flávia Batista; Langoni, Hélio [UNESP]; Popim, Regina Célia [UNESP] (FapUNIFESP (SciELO), 2021)
Objective: To analyze wound contraction and histomorphometric pattern of lesions in Wistar rats undergoing doxorubicin extravasation. Method: Sixty adult female rats were used, divided into four groups of fifteen animals: Group 1 (Control, without antidote); Group 2 (Hyaluronidase); Group 3 (Photobiomodulation), and Group 4 (Hyaluronidase + Photobiomodulation). Doxorubicin 1mg (0.5 ml) was applied subcutaneously on the animals' back, inducing the wound. Macroscopic and morphometric evaluation of the lesions was performed every two days for 28 days. On the 30th day, euthanasia was performed and the material was collected for histological evaluation. Results: The animals in the photobiomodulation and photobiomodulation + Hyaluronidase groups presented regeneration tissue with neovascularization and acute inflammation, with improvement in wound healing, which did not occur in the other groups. The contraction rates were better in those treated with photobiomodulation and photobiomodulation + Hyaluronidase, with healing percentages of 76.6% and 72.1%, respectively. Conclusion: The combination of photobiomodulation (660 nm-1 J) with topical hyaluronidase (65 UTR) proved to be effective in the process of wound healing due to extravasation of doxorubicin, and can be incorporated into the practice of clinical oncology.
Efectos de la fotobiomodulación en la contracción de heridas en ratones sometidos a la extravasación de doxorrubicina: análisis histomorfométrico
Efeitos da fotobiomodulação na contração de feridas em ratos submetidos ao extravasamento de doxorrubicina: análise histomorfométrica
Keywords: Antineoplastic Agents; Antineoplásicos; Extravasación de Materiales Terapéuticos y Diagnósticos; Extravasamento de Materiais Terapêuticos e Diagnósticos; Extravasation of Diagnostic and Therapeutic Materials; Low-Level Light Therapy; Ratas Wistar; Ratos Wistar; Rats; Terapia com Luz de Baixa Intensidade; Terapia por Luz de Baja Intensidad; Wistar